The Relationship Between Religiosity and Zakat Maal Collection: A Provincial Data Analysis in Indonesia - Ayu Dwi Utami; Febriani Astuti (Nuban Jagadhita Centre, 2026)
Purpose: This study aims to empirically analyze the relationship between religiosity, as proxied by the percentage of the Muslim population per province, and zakat maal receipts in Indonesia, with provincial Gross Regional Domestic Product (GRDP) as a control variable. This study is expected to explain why zakat receipts vary significantly across provinces in Indonesia. Methodology: The study uses a quantitative approach based on econometric analysis of panel data (pooled data) from 34 provinces in Indonesia during the 2022–2024 period. The panel data regression model selection is carried out through the Chow Test, the Hausman Test, and the LM Test, which ultimately leads to the use of a Random Effects Model. Findings: The regression results show that religiosity has a positive and significant effect on zakat maal, even after controlling for regional economic capacity. GRDP also has a positive and significant effect, confirming the role of economic capacity as a prerequisite for fulfilling zakat obligations. These findings indicate that religiosity and economic capacity are complementary, not substitutive, in encouraging zakat compliance at the provincial level, with policy implications for BAZNAS and the Ministry of Religious Affairs in designing zakat collection strategies based on religious education and economic empowerment.